2011
DOI: 10.1371/journal.pone.0022522
|View full text |Cite
|
Sign up to set email alerts
|

Underwater Application of Quantitative PCR on an Ocean Mooring

Abstract: The Environmental Sample Processor (ESP) is a device that allows for the underwater, autonomous application of DNA and protein probe array technologies as a means to remotely identify and quantify, in situ, marine microorganisms and substances they produce. Here, we added functionality to the ESP through the development and incorporation of a module capable of solid-phase nucleic acid extraction and quantitative PCR (qPCR). Samples collected by the instrument were homogenized in a chaotropic buffer compatible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 52 publications
1
59
0
Order By: Relevance
“…Already, vast oceanic distances and depths have led marine microbiologists to develop robotic systems for collection of eDNA samples (Scholin 2010). The most sophisticated platform autonomously conducts water filtration, DNA extraction, and genetic assays while deployed and transmits data via satellite (Preston et al 2011). Surveillance of airborne biological hazards has motivated similar developments (Hindson et al 2005), and engineers have also demonstrated use of unmanned aerial systems (i.e.…”
Section: Remote and Autonomous Sampling And Analysismentioning
confidence: 99%
“…Already, vast oceanic distances and depths have led marine microbiologists to develop robotic systems for collection of eDNA samples (Scholin 2010). The most sophisticated platform autonomously conducts water filtration, DNA extraction, and genetic assays while deployed and transmits data via satellite (Preston et al 2011). Surveillance of airborne biological hazards has motivated similar developments (Hindson et al 2005), and engineers have also demonstrated use of unmanned aerial systems (i.e.…”
Section: Remote and Autonomous Sampling And Analysismentioning
confidence: 99%
“…The Thaumarchaeota (or group I Archaea, formerly the Crenarchaeota (Brochier- Armanet et al, 2008;Spang et al, 2010)) also have an important role in the nitrogen cycle in coastal marine systems by oxidizing ammonia to nitrite (Kö nneke et al, 2005), thus altering the form of nitrogen available for photosynthesis and other processes in upwelled waters and deeper in the photic zone where they reside (Mincer et al, 2007;Santoro et al, 2010;Preston et al, 2011). The Thaumarchaeota have widespread global distributions, and have been estimated to comprise over 20% of marine picoplankton (Karner et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The utility of the ESP for quantifying microbial population dynamics in Monterey Bay has been demonstrated by Preston et al (2011), where microbes with predictable dynamics were quantified during the upwelling season, for technical validation of the ESP technology. Here it was shown that Thaumarchaeota abundances increase with upwelling, as expected based on their deeper distributions.…”
Section: Introductionmentioning
confidence: 99%
“…The limit of detection achieved was 100 cells per litre. An additional module, the MicroFludics Block (MFB) was later developed for in situ solid-phase nucleic acid extraction and quantitative PCR (Preston et al, 2011). The DNA was extracted and purified from 100-1000 mL samples down to 50 µL eluent aliquots.…”
Section: Sensors For Speciation Using Molecular Toolsmentioning
confidence: 99%